(untitled) (Swiss Medical Weekly, 2016)
In 2015, the international guidelines for diagnosis and treatment of pulmonary hypertension were updated. Group 3 of the current classification includes pulmonary hypertension associated with chronic obstructive pulmonary disease (COPD), interstitial lung disease, other pulmonary diseases with restrictive and obstructive pattern, sleep-disordered breathing, alveolar hypoventilation disorders, chronic exposure to high altitude, and developmental lung diseases. Pulmonary hypertension associated with COPD and interstitial lung disease is common but difficult to manage, as no long-term randomised controlled trial has been conducted with specific pulmonary arterial hypertension drugs in pulmonary hypertension associated with COPD, and the one recent RCT in pulmonary hypertension associated with interstitial lung disease had to be stopped early due to a possible increased risk of death and side effects in the treatment group. Specific treatment may thus be harmful and may worsen gas exchange as a result of possible recruitment of less oxygenised areas, i.e. by increasing ventilation-perfusion mismatch. Management of pulmonary hypertension patients with chronic lung diseases requires careful evaluation and understanding of pathophysiological mechanisms. Interestingly, mediators in PAH and in fibrotic lung disease show some overlaps. Several drugs effective in pulmonary arterial hypertensio have been evaluated for anti-fibrotic treatment in interstitial lung disease, but until today without consistent success. While new drugs with anti-fibrotic effects are now accessible, a specific evidence-based treatment for pulmonary hypertension in interstitial lung disease or COPD with or without emphysema is not yet available.